3–10 GHz self‐biased resistive‐feedback LNA with inductive source degeneration. Issue 6 (1st March 2013) - Feng, C.; Yu, X. P.; Lu, Z. H.; Lim, W. M.; Sui, W. Q.
Abstract : A 3–10 GHz self‐biased low‐noise amplifier (LNA) implemented in Global Foundries 65 nm CMOS process is presented. A novel input‐matching network employing the resistive feedback and inductive source degeneration techniques is proposed to achieve the wideband matching as well as low noise figure. The LNA exhibits a power gain of 17 ± 1 dB over 3–10 GHz with noise figure ranging from 3.5 to 4.3 dB. The fabricated LNA occupies an area of 0.15 mm 2 and draws 12 mA from 1.2 V power supply.